Analisis Kualitas Website E-Learning Menggunakan Karakteristik Standar ISO/IEC 25010:2011 - Fajar Hikmal Gunawan; Asriyanik Asriyanik; Winda Apriandari (STMIK Banjarbaru, 2021)
One of the factors that must be considered to support the success of a software is quality. Software quality can be evaluated by certain methods and used as a recommendation to be developed so that the quality of a software is maintained. This paper aims to analyze the quality of e-learning software using 8 characteristics that are included in the dimensions of software quality products from the ISO/IEC 25010 standard, which consist of functional suitability, performance efficiency, compatibility, usability, reliability, security, maintainability and portability. The results obtained after doing the calculations are the average value of the percentage of eligibility reaching 64.351% with the interpretation of